Acoustic performance of composite sandwich panels for building floors: Experimental tests and numerical-analytical simulation. (November 2020) - Proença, M.; Neves e Sousa, A.; Garrido, M.; Correia, J.R.
Abstract: Composite sandwich panels have been increasingly considered in structural applications due to their lightweight, high strength, environmental resistance, and ease of assembly. Yet, since transmission loss phenomena are usually governed by mass, their low weight renders composite sandwich panels potentially inefficient in terms of acoustic performance, a subject that has received little attention in the past. This paper presents experimental, numerical and analytical investigations about the acoustic performance of composite sandwich panels used in building construction. Standard airborne and impact sound transmission tests are performed on a full-scale composite sandwich panel, designed for structural application in building floors, and their acoustic performance is compared with the applicable code requirements. In the numerical study, a finite element model is developed to simulate the airborne sound transmission. The analytical study assesses the applicability of the reciprocity theorem to such panels. The obtained results confirmed the overall low acoustic performance of lightweight composite sandwich panel floors and pointed out the need for additional sound insulation measures. The numerical simulations presented good agreement with the experimental data, following the overall development of the experimental transmission loss curve, and predicting the dip associated with the coincidence effect. The application of the reciprocity theorem to the sandwich panel floors was validated with the experimental results and allowed for an accurate prediction of the impact sound pressure level based on the numerical results of the airborne sound reduction. Highlights: Standardized experiments regarding acoustic performance of sandwich panel building floors. Assessment of airborne sound reduction and normalized impact sound indices. Numerical modelling of airborne sound transmission of the floors. Reciprocity theorem combined with a formulation for floors with resilient layers to estimate impact noise pressure levels.